Peran Komunikasi Organisasi di Kalangan Karyawan Seven Peaks Education Jakarta - Natasha Klaresta; Agustrijanto (UNIVERSITAS KALBIS, 2022)
Seven Peaks Education is an educational consultancy migration company that applies organizational communication to its employees. In this study, there is a phenomenon where there are communication difficulties between superiors and subordinates caused by the distance between them. This research was conducted to find out how the role of organizational communication is carried out at Seven Peaks Education among the employees who work there. The object of this study is employees who work at the Seven Peaks Education company. In this study the technique used in the collection of this data is to use in-depth interviews and observation. This type of research uses descriptive type of research. The results of this study indicate that the role of organizational communication in Seven Peaks among its employees is not maximized because of the vertical and horizontal communication carried out at Seven Peaks is still mostly done online. So that it affects Seven Peaks employees.